ANALISA DAN PERANCANGAN ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) DALAM MENINGKATKAN LOYALITAS PELANGGAN PADA PT. PENTA ARTHA IMPRESSI - Adhitya Ilham Ramdhani (KILAT, 2015)
In this globalization era, a business will be successful if it is supported by technology. Many companies are competing to master of information technology, with the hope to dominate the market and gain loyal customers. Customer Relationship Management (CRM), which is a type of management that specifically discusses the theory about the handling of the relationship between the company and it’s customers with the aim of increasing the value of the company's attention in the eyes of customers. PT. PENTA ARTHA IMPRESSI require a proximity between the company and customers in order to prevent customers moving to the company's competitors and that customers feel cared for. Currently the handling of customer complaints is not maximized, because of the lack of good complaint management. This causes customer complaints had to do many times or even directly make a complaint directly to the higher order can be handled quickly and promotion made by the company could not be delivered to customers. With the web-based system design is expected to solve the problem of declining customer loyalty PT. PENTA ARTHA IMPRESSI.